House Science, Space, and Technology Subcommittee on Energy Hearing: 1 (Congressional Documents and Publications, 2015)
[...]the work prioritized by EERE is far too focused on increasing the use of today's technology, not conducting the fundamental research to lay the foundation for the next technology breakthrough. Models developed in the Office of Science's ASCR program - the subject of an Energy Subcommittee hearing earlier this year - can be used to study and improve techniques in manufacturing, renewable power, and energy efficiency, enabling the private sector to develop and bring new technology into the market without American tax dollars.